If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + -1x = 7 + 3x Solving 3 + -1x = 7 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 3 + -1x + -3x = 7 + 3x + -3x Combine like terms: -1x + -3x = -4x 3 + -4x = 7 + 3x + -3x Combine like terms: 3x + -3x = 0 3 + -4x = 7 + 0 3 + -4x = 7 Add '-3' to each side of the equation. 3 + -3 + -4x = 7 + -3 Combine like terms: 3 + -3 = 0 0 + -4x = 7 + -3 -4x = 7 + -3 Combine like terms: 7 + -3 = 4 -4x = 4 Divide each side by '-4'. x = -1 Simplifying x = -1
| x^4-6x^3+12x^2-26x-45=0 | | x-2x-10=0 | | 8x+15=78+8 | | 7x^3-7x^2*x=0 | | 2a^4*-8a^2=0 | | a^3*a^5*a=0 | | 8/4=10/x | | a^3*a^5*4=0 | | 3z/7-1=6 | | 2y=x^(2/3) | | 9x-7x+134=2x+134 | | x^2+y^2+3x-1=0 | | 2xy-6y+4=0 | | 6(p+10)=8p+16 | | 4y-13=8 | | 3(n-5)=4(n-4) | | 3ab/(4a^3) | | (((5,0.10^-3)-x)/0.10).(0,10/x)=4,64 | | (((5,0.10^-3)-x)/0.10).(0,10/x) | | 3/5k-1/5=2/5 | | 5x(2x-13)=15 | | (2x-13)=15 | | 16cos^2(x)+8cos(x)-2=0 | | -2(a+4)=6(a-2) | | 4.5z-2.5z=2.4 | | sin*2x+tg*x=-2 | | =0875 | | =.0875 | | 3x+4x+15= | | 14-6v=22 | | 10=4i-26 | | 5b+12=2b+18 |